Pengembangan Potensi Wisata di desa Wisata Yehembang Kangin Kecamatan Mendoyo Kabupaten Jembrana - Anggara, I Gusti Made Dwi Candra; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 7 No 1 (2019): VOL 7, NO 1 (2019): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2019)
Village of Yehembang Kangin is one of tourism village which has various tourism potential inside which have not been optimized as a tourism destination or tourist attraction. The purpose of this studies to know potential of tourism in the Yehembang Kangin Village Tourism and know the efforts to development of tourism potential in the Yehembang Kangin Tourism Village. The research method used in this research, is a qualitative research, where the qualitative research used, observation, in-depth interview technique and qualitative documents. The concept of tourism supporting components in formulating the existing conditions in the Yehembang Kangin Tourism Village. And data analysis technique used in this research is descriptive qualitative. The results of this research is Yehembang Kangin Village have two potensial tourism among others is natural and culture potential tourism and the effort to the development of tourism potential in the Tourism Village Yehembang Kangin there are two aspects is mapping of tourist attractions and local community empowerment in the Village Tourism Yehembang Kangin. Key Words Potential Tourism, Tourist Attractions, Yehembang Kangin Village Tourism